The Impact of Endogenous Motivations on Adoption of IT-Enabled Services: The Case of Transformative Services in the Energy Sector. (August 2013) - Wunderlich, Philipp; Kranz, Johann; Totzek, Dirk; Veit, Daniel; Picot, Arnold
Transformative services represent a crucial topic in future service research. Particularly in the energy sector, consumer adoption of transformative—often IT-enabled—services is essential to increased environmental sustainability. As adopting these services increases both individual and collective well-being, research has to delve more deeply into the origins of consumers' motivations. For this reason, this study aims at augmenting the understanding of how different types of motivation determine consumers' intention to adopt transformative services. The proposed model integrates the theory of planned behavior and the self-determination theory and is tested with survey data gathered from 462 users and 537 nonusers of home energy management services. Results indicate that consumers' motivations are major direct determinants of intentions to adopt. While this finding notably holds when consumers perceive the adoption as self-determined and internalize associated values such as environmentalism, motivations based on external rewards and feelings of compulsion matter to a lesser extent. A comparison of users and nonusers reveals important differences in motivation, in particular that extrinsic motivations tend to be more relevant for nonusers than for users.